2013
DOI: 10.1542/peds.2012-2556
|View full text |Cite
|
Sign up to set email alerts
|

Baby-Friendly Hospital Accreditation, In-Hospital Care Practices, and Breastfeeding

Abstract: When breastfeeding-initiation rates are high and evidence-based practices that support breastfeeding are common within the hospital environment, BFHI accreditation per se has little effect on both exclusive or any breastfeeding rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 27 publications
3
86
0
4
Order By: Relevance
“…In other studies conducted in other states in Nigeria, all the respondents breastfed their babies. 15,16,17,18 This is not surprising since initiation of breastfeeding is almost universal in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies conducted in other states in Nigeria, all the respondents breastfed their babies. 15,16,17,18 This is not surprising since initiation of breastfeeding is almost universal in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,25 Our study revealed that previously Baby-Friendly hospitals with the highest breastfeeding rates at the start of our project did not achieve additional increases, similar to fi ndings from a recent Australian study. 26 It is likely that the active work of becoming Baby-Friendly, including intensive provider education and a continued focus on breastfeeding best practices, is the most effective element in achieving and sustaining increases in rates of in-hospital breastfeeding. 25,26,27 Furthermore, it has been reported that full compliance with the Ten Steps among Baby-Friendly hospitals remains challenging, 28 supporting the requirement that hospitals continue Ten…”
Section: Discussionmentioning
confidence: 99%
“…'Separation' referred to mothers not experiencing intimate and continuous contact with their infant specifically in relation to skin-to-skin contact involving the placing of the naked baby prone on the mother's bare chest, though this was immediate in some studies and delayed to some extent in others (Moore et al, 2012). In high and middle income countries most new mothers room in with their babies (Declercq et al, 2013;Public Health Agency of Canada, 2009;Brodribb et al, 2013), though this was not always so (Anderson, 1989). However, such new mothers may have less in the way of this type of contact immediately following birth than that reported in some low income countries (Bornstein, 1991;Trevathen, 2011).…”
Section: Introductionmentioning
confidence: 99%